Hubungan antara Dukungan Sosial Teman Sebaya dan Resiliensi Akademik pada Mahasiswa yang Mengalami Burnout Akademik - Angelica Noverina; Agustina Agustina (Lembaga Yasin AlSys, 2026)
Final-year university students often face high academic pressure, placing them at risk of academic burnout that can hinder learning processes and thus requires strong resilience. In this context, peer social support is assumed to play an important role in strengthening students’ capacity to cope with academic pressures. This study aimed to examine the relationship between peer social support and academic resilience among students experiencing academic burnout. The study employed a quantitative survey approach involving 171 participants who completed the Student Social Support Scale (SSSS) and the Academic Resilience Scale (ARS). Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Spearman’s rho correlation in Jamovi. The results showed that peer social support had a positive and significant relationship with academic resilience, indicating that the higher the support received from peers, the higher students’ academic resilience in coping with academic burnout. These findings underscore the importance of peer social support as a protective factor that helps students endure and recover from academic pressure and may serve as a basis for developing mentoring programs and strengthening social networks in higher education settings.